Digital Competence in Higher Education: Challenges and Experiencesin AI Integration - Gaona Couto, Beatriz Bibiana; Velázquez Albo, Marco Antonio (Emerging Trends in Education, 2026)
This study analyzes Teacher Digital Competence (TDC) in a public higher education institution belonging to Mexico’s technological subsystem, with the aim of identifying the factors that influence its development. A qualitative methodology based on thematic analysis (Braun & Clarke, 2006) was applied, drawing on the experiences of 43 teachers who voluntarily participated in four focus groups. The findings reveal a positive attitude among faculty toward the integration of digital technologies, highlighting the use of generative artificial intelligence (AI) as a successful practice, particularly in the creation of teaching materials, the promotion of student engagement, and the optimization of class preparation time. However, structural factors were identified that hinder the development of digital competence and limit pedagogical innovation mediated by technology. It is concluded that strengthening TDC should be part of a comprehensive institutional strategy that provides emotional support to teachers facing the affective cost of acquiring new competencies, promotes professional development as a planned process, and fosters an organizational culture aligned with digital transformation. This is essential to harness the educational potential of generative AI, considering the faculty’s positive disposition toward its pedagogical use.